Westonci.ca is your trusted source for finding answers to a wide range of questions, backed by a knowledgeable community. Get detailed answers to your questions from a community of experts dedicated to providing accurate information. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.
Sagot :
To find a cascaded realization for the transfer function
[tex]\[ H(z) = \frac{z^2 (6z - 2)}{(z-1) \left(z^2 - \frac{1}{6}z - \frac{1}{6}\right)} \][/tex]
we will factorize both the numerator and the denominator into their respective roots and then express \( H(z) \) in terms of its zeros and poles.
### Step 1: Factorize the Numerator
The numerator of the transfer function is given by:
[tex]\[ z^2 (6z - 2) \][/tex]
We can express this in factored form as:
[tex]\[ z^2 (6z - 2) = z^2 \cdot 2(3z - 1) = 2z^2(3z - 1) \][/tex]
The numerator has roots at \( z = 0 \) and \( z = \frac{1}{3} \). Thus, the numerator can be written as:
[tex]\[ 2z^2 (z - \frac{1}{3}) \][/tex]
### Step 2: Factorize the Denominator
The denominator of the transfer function is given by:
[tex]\[ (z-1) \left(z^2 - \frac{1}{6}z - \frac{1}{6}\right) \][/tex]
We need to solve the quadratic equation:
[tex]\[ z^2 - \frac{1}{6}z - \frac{1}{6} = 0 \][/tex]
The roots of this quadratic equation are obtained using the quadratic formula:
[tex]\[ z = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \][/tex]
where \( a = 1 \), \( b = -\frac{1}{6} \), and \( c = -\frac{1}{6} \).
Solving for the roots, we get:
[tex]\[ z = \frac{\frac{1}{6} \pm \sqrt{\left(\frac{1}{6}\right)^2 + 4 \cdot \frac{1}{6}}}{2} \][/tex]
Simplifying the expression inside the square root and solving for \( z \):
[tex]\[ z = \frac{\frac{1}{6} \pm \sqrt{\frac{1}{36} + \frac{2}{3}}}{2} \][/tex]
[tex]\[ z = \frac{\frac{1}{6} \pm \sqrt{\frac{1}{36} + \frac{12}{36}}}{2} \][/tex]
[tex]\[ z = \frac{\frac{1}{6} \pm \sqrt{\frac{13}{36}}}{2} \][/tex]
[tex]\[ z = \frac{\frac{1}{6} \pm \frac{\sqrt{13}}{6}}{2} \][/tex]
[tex]\[ z = \frac{1 \pm \sqrt{13}}{12} \][/tex]
Thus, the roots of the denominator are:
[tex]\[ z_1 = \frac{1 + \sqrt{13}}{12} \approx 0.5 \][/tex]
[tex]\[ z_2 = \frac{1 - \sqrt{13}}{12} \approx -0.333 \][/tex]
And we have one more root at \( z = 1 \) from the linear factor.
So, we can write the denominator as:
[tex]\[ (z-1)(z-0.5)(z+0.333) \][/tex]
### Step 3: Construct the Transfer Function in Factored Form
Using the roots, the transfer function can be written as:
[tex]\[ H(z) = \frac{2z^2 (z - \frac{1}{3})}{(z - 1)(z - 0.5)(z + 0.333)} \][/tex]
### Step 4: Cascaded Realization
The factored form of \( H(z) \) can be realized as a series of second-order sections.
1. The first stage is:
[tex]\[ H_1(z) = \frac{z - 0}{z - 1} = \frac{z}{z - 1} \][/tex]
2. The second stage is:
[tex]\[ H_2(z) = \frac{z - 0}{z - 0.5} = \frac{z}{z - 0.5} \][/tex]
3. The third stage is:
[tex]\[ H_3(z) = \frac{2(z - \frac{1}{3})}{z + 0.333} = \frac{2(z - \frac{1}{3})}{z + 0.333} \][/tex]
So the cascaded realization of \( H(z) \) is:
[tex]\[ H(z) = H_1(z) \cdot H_2(z) \cdot H_3(z) \][/tex]
where
[tex]\[ H_1(z) = \frac{z}{z - 1} \][/tex]
[tex]\[ H_2(z) = \frac{z}{z - 0.5} \][/tex]
[tex]\[ H_3(z) = \frac{2(z - \frac{1}{3})}{z + 0.333} \][/tex]
Each of these stages can be implemented using digital filters in a cascade system.
[tex]\[ H(z) = \frac{z^2 (6z - 2)}{(z-1) \left(z^2 - \frac{1}{6}z - \frac{1}{6}\right)} \][/tex]
we will factorize both the numerator and the denominator into their respective roots and then express \( H(z) \) in terms of its zeros and poles.
### Step 1: Factorize the Numerator
The numerator of the transfer function is given by:
[tex]\[ z^2 (6z - 2) \][/tex]
We can express this in factored form as:
[tex]\[ z^2 (6z - 2) = z^2 \cdot 2(3z - 1) = 2z^2(3z - 1) \][/tex]
The numerator has roots at \( z = 0 \) and \( z = \frac{1}{3} \). Thus, the numerator can be written as:
[tex]\[ 2z^2 (z - \frac{1}{3}) \][/tex]
### Step 2: Factorize the Denominator
The denominator of the transfer function is given by:
[tex]\[ (z-1) \left(z^2 - \frac{1}{6}z - \frac{1}{6}\right) \][/tex]
We need to solve the quadratic equation:
[tex]\[ z^2 - \frac{1}{6}z - \frac{1}{6} = 0 \][/tex]
The roots of this quadratic equation are obtained using the quadratic formula:
[tex]\[ z = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \][/tex]
where \( a = 1 \), \( b = -\frac{1}{6} \), and \( c = -\frac{1}{6} \).
Solving for the roots, we get:
[tex]\[ z = \frac{\frac{1}{6} \pm \sqrt{\left(\frac{1}{6}\right)^2 + 4 \cdot \frac{1}{6}}}{2} \][/tex]
Simplifying the expression inside the square root and solving for \( z \):
[tex]\[ z = \frac{\frac{1}{6} \pm \sqrt{\frac{1}{36} + \frac{2}{3}}}{2} \][/tex]
[tex]\[ z = \frac{\frac{1}{6} \pm \sqrt{\frac{1}{36} + \frac{12}{36}}}{2} \][/tex]
[tex]\[ z = \frac{\frac{1}{6} \pm \sqrt{\frac{13}{36}}}{2} \][/tex]
[tex]\[ z = \frac{\frac{1}{6} \pm \frac{\sqrt{13}}{6}}{2} \][/tex]
[tex]\[ z = \frac{1 \pm \sqrt{13}}{12} \][/tex]
Thus, the roots of the denominator are:
[tex]\[ z_1 = \frac{1 + \sqrt{13}}{12} \approx 0.5 \][/tex]
[tex]\[ z_2 = \frac{1 - \sqrt{13}}{12} \approx -0.333 \][/tex]
And we have one more root at \( z = 1 \) from the linear factor.
So, we can write the denominator as:
[tex]\[ (z-1)(z-0.5)(z+0.333) \][/tex]
### Step 3: Construct the Transfer Function in Factored Form
Using the roots, the transfer function can be written as:
[tex]\[ H(z) = \frac{2z^2 (z - \frac{1}{3})}{(z - 1)(z - 0.5)(z + 0.333)} \][/tex]
### Step 4: Cascaded Realization
The factored form of \( H(z) \) can be realized as a series of second-order sections.
1. The first stage is:
[tex]\[ H_1(z) = \frac{z - 0}{z - 1} = \frac{z}{z - 1} \][/tex]
2. The second stage is:
[tex]\[ H_2(z) = \frac{z - 0}{z - 0.5} = \frac{z}{z - 0.5} \][/tex]
3. The third stage is:
[tex]\[ H_3(z) = \frac{2(z - \frac{1}{3})}{z + 0.333} = \frac{2(z - \frac{1}{3})}{z + 0.333} \][/tex]
So the cascaded realization of \( H(z) \) is:
[tex]\[ H(z) = H_1(z) \cdot H_2(z) \cdot H_3(z) \][/tex]
where
[tex]\[ H_1(z) = \frac{z}{z - 1} \][/tex]
[tex]\[ H_2(z) = \frac{z}{z - 0.5} \][/tex]
[tex]\[ H_3(z) = \frac{2(z - \frac{1}{3})}{z + 0.333} \][/tex]
Each of these stages can be implemented using digital filters in a cascade system.
Thank you for trusting us with your questions. We're here to help you find accurate answers quickly and efficiently. We appreciate your time. Please come back anytime for the latest information and answers to your questions. Keep exploring Westonci.ca for more insightful answers to your questions. We're here to help.